Development of A System for Monitoring and Evaluating the Performance of Civil Servants in Traffic Law Enforcement Traffic and Road Transportation - Yusuf, Cindra Dewi; Moonti, Roy Marthen; Ahmad, Ibrahim (International Journal of Law, Crime and Justice, 2024)
Law enforcement of road transportation traffic is one of the important aspects in maintaining road safety and order. However, the effectiveness of monitoring and evaluating the performance of Civil Servant Investigators (PPNS) in law enforcement is often hampered by unstructured processes and lack of transparency in reporting. This research aims to analyze the role of information technology (IT)-based system development in improving transparency, efficiency, and accountability in monitoring and evaluating PPNS performance. This research uses a qualitative method with a case study approach, which involves analyzing the application of information systems in institutions that handle traffic law enforcement. The results showed that IT systems can improve transparency by providing clear and real-time data access, increase efficiency by speeding up data processing and analysis, and strengthen accountability through auditable digital records. The study concludes that the development and implementation of IT systems in the oversight of PPNS performance not only improves the effectiveness of traffic law enforcement, but also strengthens the integrity and public trust in the institutions that carry out these tasks. The implementation of IT systems is expected to be a strategic solution in improving the quality of public services in the field of traffic law.